Support notions for belief functions - Dominiak, Adam; Eichberger, Jürgen (Economics letters, 2016)
In this note we compare several support notions for capacities and sets of multiple priors. We characterize these support notions in the context of belief functions and show how they affect the analysis of games when players face strategic ambiguity.